Masters of Russian Animation - Volume 2 - Ivanov-Vano, Ivan Petrovic; Atamanov, Lev Konstantinovic; Norstejn, Jurij Borisovic; Khrjanovsky, Andrei (image Entertainment, 2000)
The artists featured on the second volume of Image Entertainment and Jove Films' enchanting Masters of Russian Animation, in their decision to abandon the real world in favor of one over which they have complete control, knew full well the inherent power of images. Each of the twelve short films presented on the disc, spanning a broad range of styles and moods, is more astounding than the next. Unfettered by the laws of nature, the animator's vision is of the purest essence, limited only by the boundaries of their imagination (a lesson well learned by modern visionaries like Tim Burton and the Brothers Quay). Given the oppressive conditions under which these films were created - Russia has never been a bastion of free speech and unrestrained creativity - the decidedly upbeat message delivered by most of the shorts came as somewhat of a surprise ... [www.amazon.com]